Assessing performance of simplified bioassays for soil-borne pathogens in smallholder systems of western Kenya - Mutai, Joyce C.; Stewart, Jane E.; Medvecky, Beth; Dobbs, John T.; Vanek, Steven J.; Ojiem, John; Chege, Gabriel; Fonte, Steven J. (Frontiers in Plant Science, 2024)
Soil-borne pathogens cause considerable crop losses and food insecurity in smallholder systems of sub-Saharan Africa. Soil and crop testing is critical for estimating pathogen inoculum levels and potential for disease development, understanding pathogen interactions with soil nutrient and water limitations, as well as for developing informed soil health and disease management decisions. However, formal laboratory analyses and diagnostic services for pathogens are often out of reach for smallholder farmers due to the high cost of testing and a lack of local laboratories.To address this challenge, we assessed the performance of a suite of simplified soil bioassays to screen for plant parasitic nematodes (e.g., Meloidogyne, Pratylenchus) and other key soil-borne pathogens (Pythium and Fusarium). We sampled soils from on-farm trials in western Kenya examining the impact of distinct nutrient inputs (organic vs. synthetic) on bean production. Key soil health parameters and common soil-borne pathogens were evaluated using both simple bioassays and formal laboratory methods across eleven farms, each with three nutrient input treatments (66 samples in total). The soil bioassays, which involved counting galls on lettuce roots and lesions on soybean were well correlated with the abundance of gall forming (Meloidogyne) and root lesion nematodes (e.g., Pratylenchus) recovered in standard laboratory-based extractions.Effectiveness of a Fusarium bioassay, involving the counting of lesions on buried bean stems, was verified via sequencing and a pathogenicity test of cultured Fusarium strains. Finally, a Pythium soil bioassay using selective media clearly distinguished pathogen infestation of soils and infected seeds. When examining management impact on nematode communities, soils amended with manure had fewer plant parasites and considerably more bacterivore and fungivore nematodes compared to soils amended with synthetic N and P. Similarly, Pythium presence was 35% lower in soils amended with manure, while the Fusarium assays indicated 23% higher Fusarium infection in plots with amended manure. Our findings suggest that relatively simple bioassays can be used to help farmers assess soil-borne pathogens in a timely manner, with minimal costs, thus enabling them to make informed decisions on soil health and pathogen management.